HUBUNGAN BEBAN KERJA, FAKTOR DEMOGRAFI, LOCUS OF CONTROL DAN HARGA DIRI TERHADAP BURNOUT SYNDROME PADA PERAWAT PELAKSANA IRD RSUP SANGLAH - Sari, Dian Yunita (Coping: Community of Publishing in Nursing; Vol 3 No 2 (2015): JURNAL EDISI MEI-AGUSTUS 2015, 2015)
Burnout syndrome is a collection of physical symptoms, psychological and destructive mental fatigue as a result of the work that is monotonous and oppressive thatis found in the nurses. This research was an observational correlation study with cross sectional design. The total sample involved 53 associate nurses in Medical Surgical and Ratna ward of Sanglah Hospital determine throughThe Total Sampling Technique. The tests are usedwere Kendal Tau test and Contingency coefficient (p value<?, ?=0,05). The results of research showed there were significant relationships between workload (p value=0,006, r=0.371), age (p value=0,033, r=0,287), marital status (p value=0,015, r=0,371), years of working (p value = 0,000, r=0,597), locus of control (p value = 0,000,r = 0,475) and self-esteem (p value=0,024, r=-0,304) with burnout syndrome. However, there is no significant relationship between gender (p value=0,415, p value>0,05) and level of education (p value=0,463, p value>0,05) with burnout syndrome. Burnout syndrome can cause decreased effectiveness of work, social relationships between colleagues becomes tenuous, and the resulting negative feelings toward patients. Thus, the nurses are expected to increase self-esteem and internal locus of control to build positive coping of work’s stressors.
Keywords: Burnout Syndrome, Demographic Factors,Locus of Control, Self-Esteem,Workload